Influence of Discrimination Experience and Disability Acceptance on Life Satisfaction: Focusing on Comparison of Elders with Disabilities with Adult with Disabilities - Lee, Young Ran; Kim, Yun-Jeong (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to identify the influence of the discrimination experience and the disability acceptance on the life satisfaction from the elderly with disabilities and the adult disabilities. Methods/Statistical analysis: The crossover analysis, t-test, correlation analysis and regression analysis were performed using SPSS 21.0.Findings: First, Identify the difference in the socio-demographic, health and disability characteristics between the elderly with disabilities and the adult with disabilities. Second, identify the difference in the discrimination experience, disability acceptance and life satisfaction between the elderly with disabilities and the adult with disabilities. Third, identify the influence of the discrimination experience and the disability acceptance on the life satisfaction of the elderly with disabilities and the adult with disabilities.Improvements/Applications: The disability acceptance has the highest influence on the life satisfaction. Therefore, this study identified that the disability acceptance has more influence on the life satisfaction than the discrimination experience and the quality of life in the elderly with disabilities is lower compared with the adult with disabilities and suggested the welfare alternatives for that